A kind of mildew-proof seam beautifying agent and preparation method thereof

The mildew-proof seam beautifying agent addresses mold growth and brittleness issues in caulking agents by forming a three-dimensional network structure with specific components, ensuring strong adhesion, toughness, and mildew resistance in humid environments.

CN116285822BActive Publication Date: 2024-12-27ANHUI NIUYUAN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310384209.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-06
Publication Date
2024-12-27
Estimated Expiration
2043-04-06

AI Technical Summary

Technical Problem

Existing caulking agents for tile gaps in humid environments suffer from mold growth, poor adhesion, brittleness, and cracking, failing to provide adequate toughness and mildew resistance.

Method used

A mildew-proof seam beautifying agent comprising components A and B, with specific ratios of epoxy resin, curing agent, defoaming agent, antibacterial agent, pigment, thixotropic agent, and nanofibers, forming a three-dimensional network structure to enhance adhesion, toughness, and mildew resistance.

Benefits of technology

The agent achieves excellent adhesion, toughness, crack resistance, mildew-proof effects, and high gloss, suitable for humid environments like bathrooms, with improved construction performance and flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004173249980000111
    Figure BDA0004173249980000111
  • Figure BDA0004173249980000112
    Figure BDA0004173249980000112
  • Figure BDA0004173249980000121
    Figure BDA0004173249980000121
Patent Text Reader

Abstract

The invention discloses an anti-mildew and beauty seam agent and a preparation method thereof. The anti-mildew and beauty seam agent comprises an A component and a B component, wherein the raw materials for preparing the A component, by weight, comprise: 70-90 parts of epoxy resin, 0.1-0.5 parts of defoaming agent, 0.05-0.3 parts of antibacterial agent, 5-15 parts of pigment, 3-6 parts of thixotropic agent, and 0.5-1.5 parts of nanofiber; the raw materials for preparing the B component, by weight, comprise: 75-90 parts of curing agent, 0.1-0.5 parts of defoaming agent, 1-3 parts of waterproofing agent, 2-6 parts of diluent, 3-7 parts of nanofiber, and 3-6 parts of thixotropic agent; the anti-mildew and beauty seam agent prepared by the invention has certain bonding and fixing property, good toughness, anti-cracking, good hardness and antibacterial and anti-mildew effect, and also has good construction performance (anti-sagging property, no sagging), high gloss, is suitable for being used as a beauty seam agent for tile paving, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of coatings, and its classification number is C09D163 / 00. Specifically, it relates to an anti-mildew and beautifying seam agent and a preparation method thereof. Background Art

[0002] Ceramic tiles are a widely used decoration material. Usually, white cement is used to fill the gaps between the tiles after they are laid. Although it can achieve the effects of beauty and anti-fouling, its glossiness is low and it will also become moldy and black. In recent years, a new type of caulking material has appeared on the market - caulking agent. Caulking agent is an upgraded product of caulking agent. It has a variety of colors, is easy to construct, and is significantly better than caulking agent in terms of decorativeness and practicality.

[0003] Since caulking agents are often used in tile gaps in humid spaces such as bathrooms, long-term exposure to a humid environment will make it easy for mold to grow in the gaps and cause the gaps to turn black, which not only affects the appearance but also affects human health. In addition, the commonly used caulking agents include single-component polymer emulsion caulking agents and two-component epoxy caulking agents, but the single-component polymer emulsion caulking agents have disadvantages such as poor adhesion and easy falling off. Although the two-component epoxy caulking agent has strong adhesion, the epoxy resin of the two-component epoxy caulking agent is generally a thermosetting resin, which has problems such as high brittleness, which will cause the caulking to crack easily after caulking, affecting the caulking effect.

[0004] Patent CN112322236B discloses an antibacterial caulking agent and its preparation method and application. It adopts hydrogenated epoxy resin to improve the yellowing resistance of the caulking agent. Under the joint action of urea-formaldehyde melamine resin, isocyanate and antibacterial agent, the antibacterial rate is as high as 99.9%. However, it does not solve the problems of toughness and strength.

[0005] Patent CN 111410890A discloses a two-component anti-cracking seam beautifier and its preparation method, which uses polyamide-modified nano titanium dioxide, and under the joint action of a coupling agent, an emulsifier, and a pH adjuster, makes the seam beautifier less likely to crack, but does not solve the problem that the seam beautifier is prone to mold in a humid environment. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present invention provides an anti-mildew and beautifying seam agent, comprising component A and component B, wherein the raw materials for preparing component A, by weight, include: 70-90 parts of epoxy resin, 0.1-0.5 parts of defoaming agent, 0.05-0.3 parts of antibacterial agent, 5-15 parts of pigment, 3-6 parts of thixotropic agent, 0.5-1.5 parts of nanofiber, and the raw materials for preparing component B, by weight, include: 75-90 parts of curing agent, 0.1-0.5 parts of defoaming agent, 1-3 parts of waterproofing agent, 2-6 parts of diluent, 3-7 parts of nanofiber, and 3-6 parts of thixotropic agent.

[0007] Further preferably, the mildew-proofing and beautifying seam agent comprises component A and component B, wherein the raw materials for preparing component A, by weight, comprise: 85-90 parts of epoxy resin, 0.1-0.4 parts of defoaming agent, 0.08-0.2 parts of antibacterial agent, 5-10 parts of pigment, 4-6 parts of thixotropic agent, 0.8-1.2 parts of nanofiber, and the raw materials for preparing component B, by weight, comprise: 80-85 parts of curing agent, 0.1-0.3 parts of defoaming agent, 1-2 parts of waterproofing agent, 2-5 parts of diluent, 4-6 parts of nanofiber, and 4-6 parts of thixotropic agent.

[0008] Further preferably, the mildew-proofing and beautifying seam agent comprises component A and component B, wherein the raw materials for preparing component A, by weight, comprise: 85.1 parts of epoxy resin, 0.3 parts of defoaming agent, 0.1 parts of antibacterial agent, 9 parts of pigment, 4.5 parts of thixotropic agent, and 1 part of nanofiber; the raw materials for preparing component B, by weight, comprise: 83.8 parts of curing agent, 0.2 parts of defoaming agent, 1.5 parts of waterproofing agent, 4 parts of diluent, 5 parts of nanofiber, and 5.5 parts of thixotropic agent.

[0009] Further preferably, the pigment is pearl powder and iron oxide, the mass ratio of the two is 1:1, the thixotropic agent is fumed silica and / or bentonite, and the diluent is benzyl alcohol.

[0010] More preferably, the thixotropic agent is fumed silica, and its average particle size is 10 μm.

[0011] Preferably, the weight ratio between the epoxy resin and the curing agent is (85-90): (80-85).

[0012] Further preferably, the weight ratio between the epoxy resin and the curing agent is (85-88):(82-84).

[0013] Further preferably, the weight ratio between the epoxy resin and the curing agent is 85.1:83.8.

[0014] Preferably, the epoxy resin includes at least one of bisphenol A epoxy resin, halogenated bisphenol A epoxy resin, bisphenol F epoxy resin, glycerol epoxy resin, novolac epoxy resin, and ethylene glycol epoxy resin.

[0015] More preferably, the epoxy resin is bisphenol A epoxy resin.

[0016] Preferably, the epoxy resin has a viscosity of 10,000-16,000 cps at 25° C. and an epoxy equivalent of 170-200 g / mol.

[0017] More preferably, the epoxy resin has a viscosity of 11000-16000 cps at 25° C. and an epoxy equivalent of 180-200 g / mol.

[0018] More preferably, the epoxy resin has a viscosity of 12000-15000 cps at 25° C. and an epoxy equivalent of 184-190 g / mol.

[0019] Preferably, the average particle size of the antibacterial agent is 5-15 μm.

[0020] More preferably, the average particle size of the antibacterial agent is 8-12 μm.

[0021] More preferably, the average particle size of the antibacterial agent is 10 μm.

[0022] More preferably, the antibacterial agent is an inorganic silver-based glass carrier antibacterial agent.

[0023] Preferably, the curing agent includes at least one of aliphatic amine curing agent, polyamide curing agent and aromatic curing agent.

[0024] More preferably, the curing agent is a fatty amine curing agent.

[0025] Preferably, the curing agent has a viscosity of 500-2500 cps at 25° C. and an amine value of 180-220 mg KOH / g.

[0026] More preferably, the curing agent has a viscosity of 800-2200 cps at 25° C. and an amine value of 190-210 mgKOH / g.

[0027] More preferably, the curing agent has a viscosity of 1000-2000 cps at 25° C. and an amine value of 190-210 mgKOH / g.

[0028] Preferably, the average particle size of the nanofibers is 0.5-1.5 μm and the density is 1.5-2.0 g / cm 3 , aspect ratio is 5-20.

[0029] More preferably, the average particle size of the nanofibers is 0.6-1.2 μm, and the density is 1.8-2.0 g / cm 3 , aspect ratio is 8-20.

[0030] More preferably, the average particle size of the nanofibers is 0.8-1.0 μm, and the density is 1.9 g / cm 3 , aspect ratio is 10-20.

[0031] Preferably, the defoaming agent is a polysiloxane defoaming agent.

[0032] Further preferably, the defoaming agent is a modified polysilicone mixture containing hydrophobic ions.

[0033] The second aspect of the present invention provides a method for preparing a mildew-proof seam-beautifying agent, comprising the following steps:

[0034] (1) Preparation of component A;

[0035] Mix epoxy resin, defoamer, antibacterial agent and nanofiber according to weight and stir for 20-30 minutes, then add pigment and stir, then continue to add thixotropic agent, evacuate and stir for 60-70 minutes to obtain component A;

[0036] (2) Preparation of component B.

[0037] The curing agent, defoaming agent, flow stopper, diluent and nanofiber are mixed and stirred according to weight for 20-30 minutes, and then the thixotropic agent is added. After vacuuming, the mixture is stirred for 40-50 minutes to obtain component B.

[0038] The applicant found that when the epoxy value of the epoxy resin is limited to 170-200g / mol and the viscosity is 11000-16000cps, although the overall hardness of the caulking agent can be made stronger, the viscosity is large and difficult to construct, and its flexibility is also poor. Therefore, on this basis, the applicant limits the amine value of the curing agent to 180-220mg KOH / g, and the viscosity at 25°C is 800-2200cps. Under the joint action of the diluent benzyl alcohol, on the one hand, the viscosity of the system is adjusted, while ensuring certain bonding properties, the problem of high viscosity and difficulty in construction is avoided, and the flexibility of the coating is improved. On the other hand, the problem of too high amine value of the curing agent, which will lead to a decrease in hardness, is avoided, so that the hardness of the caulking agent is increased to 68D. However, it is found that this may be due to the fact that the epoxy resin is a thermosetting resin. Although a certain hardness performance is guaranteed, the problem of excessive brittleness will occur.

[0039] After extensive research, the applicant unexpectedly discovered that the average particle size of the added 3 Nanofibers with an aspect ratio of 10-20 can solve this problem. This may be because the system forms a three-dimensional network structure after the addition of nanofibers. At the same time, the flexibility of the nanofibers themselves can improve the overall toughness of the system. At the same time, the weight of the nanofibers in component A is limited to 0.8-1.2 parts, and the weight of the nanofibers in component B is limited to 4-6 parts. The problem of excessive addition of nanofibers causing agglomeration and decreased glossiness is avoided. The tensile strength of the paint film is increased to 13MPa, the hardness is increased to 68D, and the glossiness is increased to 120. At the same time, the anti-sagging performance of the seam beautifier is further improved, and its sag is only 1mm.

[0040] In addition, the applicant unexpectedly discovered that by limiting the weight ratio of bisphenol A epoxy resin and aliphatic amine curing agent to (85-90): (80-85), while ensuring the hardness and tensile strength properties of the caulking agent, the mildew resistance of the caulking agent was unexpectedly improved. It may be that the bisphenol A epoxy resin and aliphatic amine curing agent at this weight ratio can better wrap the 10 μm antibacterial agent, so that the antibacterial agent can be evenly dispersed in the three-dimensional network, avoiding the problem of silver components in the antibacterial agent being oxidized by air and thus causing the antibacterial performance to decrease. When the caulking agent is at a temperature of 25-30°C and a relative humidity of not less than 85%, the mildew growth area on the surface of the caulking agent is 0% after seven days, and the mildew resistance level is 0.

[0041] Beneficial effects: The mildew-proof caulking agent prepared by the present invention has certain adhesive fixation, good toughness, crack resistance, good hardness and antibacterial and mildew-proof effects, and also has good construction performance (anti-sagging, no sagging), high gloss, and is suitable for relatively humid environments such as bathrooms and kitchens. The present invention also provides a preparation method of the mildew-proof caulking agent, which is simple in process and operation. The obtained mildew-proof caulking agent can meet market demand, solves the problem of excessive brittleness of thermosetting resins in the prior art, and is suitable for use as a caulking agent for tile paving, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 : The steel sheet required for the tensile strength test of the mildew-proof and beautifying seam agents prepared in Examples 1-3 and Comparative Examples 1-4. Example

[0043] Example 1

[0044] A mildew-proof seam beautifying agent comprises a component A and a component B, wherein the raw materials for preparing the component A, by weight, comprise: 85.1 parts of epoxy resin, 0.3 parts of defoaming agent, 0.1 parts of antibacterial agent, 9 parts of pigment, 4.5 parts of thixotropic agent, and 1 part of nanofiber; and the raw materials for preparing the component B, by weight, comprise: 83.8 parts of curing agent, 0.2 parts of defoaming agent, 1.5 parts of waterproofing agent, 4 parts of diluent, 5 parts of nanofiber, and 5.5 parts of thixotropic agent.

[0045] The epoxy resin is a bisphenol A epoxy resin with a viscosity of 12000-15000 cps at 25° C. and an epoxy equivalent of 184-190 g / mol. It is purchased from Xiamen Xinya Applied Materials Co., Ltd. and has a brand name of NPEL-128.

[0046] The defoamer is a modified polysilicone mixture containing hydrophobic ions, purchased from Shanghai Dodi Polymer Materials Co., Ltd., with a brand number of 5800.

[0047] The average particle size of the antibacterial agent is 10 μm. The antibacterial agent is an inorganic silver-based glass carrier antibacterial agent purchased from Dingxian (Shanghai) Technology Co., Ltd. with a brand name of PG-701S2.

[0048] The pigment is pearl powder and iron oxide, and the mass ratio of the two is 1:1. The pearl powder is purchased from Ruimi New Materials (Jiangsu), and the iron oxide is purchased from Guangzhou Lai Desheng Pigment Co., Ltd.

[0049] The thixotropic agent is fumed silica with an average particle size of 10 μm, purchased from Hubei Huifu Nanomaterials Co., Ltd. with a brand name of HL-200.

[0050] The average particle size of the nanofibers is 0.8-1.0 μm, and the density is 1.9 g / cm 3 , with an aspect ratio of 10-20, is a new type of needle-shaped fiber sub-nano material in the form of composite twin crystals of silicate and sulfate, purchased from Hubei Xiwei Material Technology Co., Ltd., with a brand name of NF-808.

[0051] The curing agent is a fatty amine curing agent with a viscosity of 1000-2000 cps at 25° C. and an amine value of 190-210 mgKOH / g. It is purchased from Dongguan Tuoxin Composite Materials Co., Ltd. and has a brand name of TX-1682-S3.

[0052] The weight ratio of the epoxy resin to the curing agent is 85.1:83.8.

[0053] The waterproofing agent was purchased from Foshan Sanjingli Caimeiyi Electronic Materials Co., Ltd. with the brand name OT-801.

[0054] The diluent is benzyl alcohol, purchased from Xiamen Xinya Applied Materials Co., Ltd., with the brand name XSJ-001.

[0055] A method for preparing a mildew-proof seam-beautifying agent comprises the following steps:

[0056] (1) Preparation of component A;

[0057] Epoxy resin, defoamer, antibacterial agent and nanofiber were mixed and stirred for 25 minutes according to weight, and then pigment was added and mixed and stirred for 10 minutes. After that, thixotropic agent was added, and vacuum was evacuated until the vacuum negative pressure value reached -1, and component A was obtained after stirring for 65 minutes.

[0058] (2) Preparation of component B.

[0059] The curing agent, defoaming agent, flow-stopping agent, diluent and nanofiber were mixed and stirred according to weight for 25 minutes, and then the thixotropic agent was added. The mixture was evacuated until the vacuum negative pressure value reached -1, and the component B was obtained after stirring for 45 minutes.

[0060] Example 2

[0061] A mildew-proof seam beautifying agent comprises a component A and a component B, wherein the raw materials for preparing the component A, by weight, comprise: 90 parts of epoxy resin, 0.3 parts of defoaming agent, 0.3 parts of antibacterial agent, 9 parts of pigment, 4.5 parts of thixotropic agent, and 1.5 parts of nanofiber; and the raw materials for preparing the component B, by weight, comprise: 86 parts of curing agent, 0.2 parts of defoaming agent, 2 parts of waterproofing agent, 4 parts of diluent, 7 parts of nanofiber, and 5.5 parts of thixotropic agent.

[0062] The epoxy resin is a bisphenol A epoxy resin with a viscosity of 12000-15000 cps at 25° C. and an epoxy equivalent of 184-190 g / mol. It is purchased from Xiamen Xinya Applied Materials Co., Ltd. and has a brand name of NPEL-128.

[0063] The defoamer is a modified polysilicone mixture containing hydrophobic ions, purchased from Shanghai Dodi Polymer Materials Co., Ltd., with a brand number of 5800.

[0064] The average particle size of the antibacterial agent is 10 μm. The antibacterial agent is an inorganic silver-based glass carrier antibacterial agent purchased from Dingxian (Shanghai) Technology Co., Ltd. with a brand name of PG-701S2.

[0065] The pigment is pearl powder and iron oxide, and the mass ratio of the two is 1:1. The pearl powder is purchased from Ruimi New Materials (Jiangsu), and the iron oxide is purchased from Guangzhou Lai Desheng Pigment Co., Ltd.

[0066] The thixotropic agent is fumed silica with an average particle size of 10 μm, purchased from Hubei Huifu Nanomaterials Co., Ltd. with a brand name of HL-200.

[0067] The average particle size of the nanofibers is 0.8-1.0 μm, and the density is 1.9 g / cm 3 , with an aspect ratio of 10-20, is a new type of needle-shaped fiber sub-nano material in the form of composite twin crystals of silicate and sulfate, purchased from Hubei Xiwei Material Technology Co., Ltd., with a brand name of NF-808.

[0068] The curing agent is a fatty amine curing agent with a viscosity of 1000-2000 cps at 25° C. and an amine value of 190-210 mgKOH / g. It is purchased from Dongguan Tuoxin Composite Materials Co., Ltd. and has a brand name of TX-1682-S3.

[0069] The weight ratio of the epoxy resin to the curing agent is 90:86.

[0070] The waterproofing agent was purchased from Foshan Sanjingli Caimeiyi Electronic Materials Co., Ltd. with the brand name OT-801.

[0071] The diluent is benzyl alcohol, purchased from Xiamen Xinya Applied Materials Co., Ltd., with the brand name XSJ-001.

[0072] A method for preparing a mildew-proof seam-beautifying agent comprises the following steps:

[0073] (1) Preparation of component A;

[0074] Epoxy resin, defoamer, antibacterial agent and nanofiber were mixed and stirred for 25 minutes according to weight, and then pigment was added and mixed and stirred for 10 minutes. After that, thixotropic agent was added, and vacuum was evacuated until the vacuum negative pressure value reached -1, and component A was obtained after stirring for 65 minutes.

[0075] (2) Preparation of component B.

[0076] The curing agent, defoaming agent, flow-stopping agent, diluent and nanofiber were mixed and stirred according to weight for 25 minutes, and then the thixotropic agent was added. The mixture was evacuated until the vacuum negative pressure value reached -1, and the component B was obtained after stirring for 45 minutes.

[0077] Example 3

[0078] A mildew-proof seam beautifying agent comprises a component A and a component B, wherein the raw materials for preparing the component A, by weight, comprise: 75 parts of epoxy resin, 0.2 parts of defoaming agent, 0.05 parts of antibacterial agent, 9 parts of pigment, 4.5 parts of thixotropic agent, and 0.5 parts of nanofiber; and the raw materials for preparing the component B, by weight, comprise: 75 parts of curing agent, 0.2 parts of defoaming agent, 1.5 parts of waterproofing agent, 4 parts of diluent, 4 parts of nanofiber, and 5.5 parts of thixotropic agent.

[0079] The epoxy resin is a bisphenol A epoxy resin with a viscosity of 12000-15000 cps at 25° C. and an epoxy equivalent of 184-190 g / mol. It is purchased from Xiamen Xinya Applied Materials Co., Ltd. and has a brand name of NPEL-128.

[0080] The defoamer is a modified polysilicone mixture containing hydrophobic ions, purchased from Shanghai Dodi Polymer Materials Co., Ltd., with a brand number of 5800.

[0081] The average particle size of the antibacterial agent is 10 μm. The antibacterial agent is an inorganic silver-based glass carrier antibacterial agent purchased from Dingxian (Shanghai) Technology Co., Ltd. with a brand name of PG-701S2.

[0082] The pigment is pearl powder and iron oxide, and the mass ratio of the two is 1:1. The pearl powder is purchased from Ruimi New Materials (Jiangsu), and the iron oxide is purchased from Guangzhou Lai Desheng Pigment Co., Ltd.

[0083] The thixotropic agent is fumed silica with an average particle size of 10 μm, purchased from Hubei Huifu Nanomaterials Co., Ltd. with a brand name of HL-200.

[0084] The average particle size of the nanofibers is 0.8-1.0 μm, and the density is 1.9 g / cm 3 , with an aspect ratio of 10-20, is a new type of needle-shaped fiber sub-nano material in the form of composite twin crystals of silicate and sulfate, purchased from Hubei Xiwei Material Technology Co., Ltd., with a brand name of NF-808.

[0085] The curing agent is a fatty amine curing agent with a viscosity of 1000-2000 cps at 25° C. and an amine value of 190-210 mgKOH / g. It is purchased from Dongguan Tuoxin Composite Materials Co., Ltd. and has a brand name of TX-1682-S3.

[0086] The weight ratio of the epoxy resin to the curing agent is 75:75.

[0087] The waterproofing agent was purchased from Foshan Sanjingli Caimeiyi Electronic Materials Co., Ltd. with the brand name OT-801.

[0088] The diluent is benzyl alcohol, purchased from Xiamen Xinya Applied Materials Co., Ltd., with the brand name XSJ-001.

[0089] A method for preparing a mildew-proof seam-beautifying agent comprises the following steps:

[0090] (1) Preparation of component A;

[0091] Epoxy resin, defoamer, antibacterial agent and nanofiber were mixed and stirred for 25 minutes according to weight, and then pigment was added and mixed and stirred for 10 minutes. After that, thixotropic agent was added, and vacuum was evacuated until the vacuum negative pressure value reached -1, and component A was obtained after stirring for 65 minutes.

[0092] (2) Preparation of component B.

[0093] The curing agent, defoaming agent, flow-stopping agent, diluent and nanofiber were mixed and stirred according to weight for 25 minutes, and then the thixotropic agent was added. The mixture was evacuated until the vacuum negative pressure value reached -1, and the component B was obtained after stirring for 45 minutes.

[0094] Comparative Example 1

[0095] The curing agent is a fatty amine curing agent with a viscosity of 90-150 mPa.s at 25° C. and an amine value of 600-700 mg KOH / g. It is purchased from Jinan Yisheng Resin Co., Ltd., and the rest is the same as in Example 1.

[0096] Comparative Example 2

[0097] A mildew-proof seam beautifying agent comprises a component A and a component B, wherein the raw materials for preparing the component A, by weight, comprise: 85.1 parts of epoxy resin, 0.3 parts of defoaming agent, 0.1 parts of antibacterial agent, 9 parts of pigment, 5.5 parts of thixotropic agent, and the raw materials for preparing the component B, by weight, comprise: 83.8 parts of curing agent, 0.2 parts of defoaming agent, 1.5 parts of waterproofing agent, 4 parts of diluent, and 10.5 parts of thixotropic agent.

[0098] The epoxy resin is a bisphenol A epoxy resin with a viscosity of 12000-15000 cps at 25° C. and an epoxy equivalent of 184-190 g / mol. It is purchased from Xiamen Xinya Applied Materials Co., Ltd. and has a brand name of NPEL-128.

[0099] The defoamer is a modified polysilicone mixture containing hydrophobic ions, purchased from Shanghai Dodi Polymer Materials Co., Ltd., with a brand number of 5800.

[0100] The average particle size of the antibacterial agent is 10 μm. The antibacterial agent is an inorganic silver-based glass carrier antibacterial agent purchased from Dingxian (Shanghai) Technology Co., Ltd. with a brand name of PG-701S2.

[0101] The pigment is pearl powder and iron oxide, and the mass ratio of the two is 1:1. The pearl powder is purchased from Ruimi New Materials (Jiangsu), and the iron oxide is purchased from Guangzhou Lai Desheng Pigment Co., Ltd.

[0102] The thixotropic agent is fumed silica with an average particle size of 10 μm, purchased from Hubei Huifu Nanomaterials Co., Ltd. with a brand name of HL-200.

[0103] The curing agent is a fatty amine curing agent with a viscosity of 1000-2000 cps at 25° C. and an amine value of 190-210 mgKOH / g. It is purchased from Dongguan Tuoxin Composite Materials Co., Ltd. and has a brand name of TX-1682-S3.

[0104] The waterproofing agent was purchased from Foshan Sanjingli Caimeiyi Electronic Materials Co., Ltd. with the brand name OT-801.

[0105] The diluent is benzyl alcohol, purchased from Xiamen Xinya Applied Materials Co., Ltd., with the brand name XSJ-001.

[0106] A method for preparing a mildew-proof seam-beautifying agent comprises the following steps:

[0107] (1) Preparation of component A;

[0108] Epoxy resin, defoamer, antibacterial agent and nanofiber were mixed and stirred for 25 minutes according to weight, and then pigment was added and mixed and stirred for 10 minutes. After that, thixotropic agent was added, and vacuum was evacuated until the vacuum negative pressure value reached -1, and component A was obtained after stirring for 65 minutes.

[0109] (2) Preparation of component B.

[0110] The curing agent, defoaming agent, flow-stopping agent, diluent and nanofiber were mixed and stirred according to weight for 25 minutes, and then the thixotropic agent was added. The mixture was evacuated until the vacuum negative pressure value reached -1, and the component B was obtained after stirring for 45 minutes.

[0111] Comparative Example 3

[0112] The weight ratio between the epoxy resin and the curing agent was changed to 80:70, and the rest was the same as in Example 1.

[0113] Comparative Example 4

[0114] A mildew-proof seam beautifying agent comprises a component A and a component B, wherein the raw materials for preparing the component A, by weight, comprise: 85.1 parts of epoxy resin, 0.3 parts of defoaming agent, 0.1 parts of antibacterial agent, 9 parts of pigment, 2.5 parts of thixotropic agent, and 4 parts of nanofiber; the raw materials for preparing the component B, by weight, comprise: 83.8 parts of curing agent, 0.2 parts of defoaming agent, 1.5 parts of waterproofing agent, 4 parts of diluent, 7 parts of nanofiber, and 3.5 parts of thixotropic agent; and the rest are the same as in Example 1.

[0115] Performance Evaluation

[0116] The performance of the mildew-proof seam beautifying agents prepared in Examples 1-3 and Comparative Examples 1-4 was tested;

[0117] (1) Mildew test: Tested according to the test standard GB / T1741-2007.

[0118] (2) Bond strength test: Test according to GB / T 5210 9.4.2. Apply the sample evenly to the unglazed brick surface with a thickness of 1mm and cure for 7 days. The test base is an unglazed brick that complies with 7.11.2.1 of JC / T547-2017. After the specimen is cured for 6 days under standard conditions, the test combination of 9.4.2 of GB / T 5210-2006 is adopted, and the test is carried out according to 9.5 of GB / T 5210-2006 on the 7th day. The test column diameter is 20mm. The average value of the middle 6 groups of data should be taken as the test result, accurate to

[0119] 0.1MPa.

[0120] (3) Tensile strength (T / MPa>6MPa) test: At room temperature (23℃±2℃), apply the anti-mildew caulking agent to 1 cm of the steel sheet. Two sheets are overlapped and a 2 kg weight is pressed on the overlap. Three groups are prepared and tested with a tensile machine after 48 hours.

[0121] (4) Gloss test: Use a 60° gloss meter (model DR60A) to test the gloss of the anti-mildew caulking agent.

[0122] (5) Hardness test: Measure with a Shore A or D hardness tester in accordance with the provisions of GB / T 531.1-2008. Standard curing for 7 days. The specimen thickness is 6 mm. The value of the indicator device should be read after 3 ± 1 s.

[0123] (6) Flexibility test: Conducted in accordance with GB / T 1748-79. The specimen film thickness is 1 mm, standard curing is 7 days, and no cracks of Φ50 mm are found, which is excellent, otherwise it is poor.

[0124] (7) Determination of curing time: The anti-mildew and anti-seam agents of the examples and comparative examples were cured at 25° C., and their curing time was measured.

[0125] (8) Sag test: According to test step A in GB / T 13477.6, the test conditions are temperature: (23 ±

[0126] 2)℃, time: 24h. The internal dimension width of the cross section of the sag die groove should be (10.0±0.2)

[0127] mm, the depth should be (10.0±0.2) mm, and the length should be (150±0.2) mm.

[0128] 1. The above test was performed on Example 1. The test results are shown in Table 1.

[0129] Table 1

[0130]

[0131] 2. Hardness, glossiness, mildew and tensile strength were tested on Examples 2-3 and Comparative Examples 1-3. The test results are shown in Table 2.

[0132] Table 2

[0133]

[0134]

Claims

1. A mildew-proof seam-beautifying agent, characterized in that: It comprises component A and component B, wherein the raw materials for preparing component A, by weight, comprise: 85.1 parts of epoxy resin, 0.3 parts of defoaming agent, 0.1 parts of antibacterial agent, 9 parts of pigment, 4.5 parts of thixotropic agent, 1 part of nanofiber, and the raw materials for preparing component B, by weight, comprise: 83.8 parts of curing agent, 0.2 parts of defoaming agent, 1.5 parts of waterproofing agent, 4 parts of diluent, 5 parts of nanofiber, and 5.5 parts of thixotropic agent; The epoxy resin is a bisphenol A epoxy resin, with a viscosity of 12000-15000 cps at 25° C., an epoxy equivalent of 184-190 g / mol, and a brand of NPEL-128; The defoamer is a modified polysilicone mixture containing hydrophobic ions, with a brand number of 5800; The average particle size of the antibacterial agent is 10 μm, and the antibacterial agent is an inorganic silver-based glass carrier antibacterial agent with a brand name of PG-701S2; The pigment is pearl powder and iron oxide, and the mass ratio of the two is 1:1; The thixotropic agent is fumed silica, with an average particle size of 10 μm and a brand name of HL-200; The average particle size of the nanofibers is 0.8-1.0 μm, and the density is 1.9 g / cm 3 , with an aspect ratio of 10-20, is a new type of needle-shaped fiber sub-nano material in the form of composite twin crystals of silicate and sulfate, with the brand name NF-808; The curing agent is a fatty amine curing agent, with a viscosity of 1000-2000cps at 25°C, an amine value of 190-210mgKOH / g, and a brand name of TX-1682-S3; The weight ratio of the epoxy resin to the curing agent is 85.1:83.8; The waterproofing agent is OT-801. The diluent is benzyl alcohol.

2. A method for preparing the mildew-proof seam-beautifying agent according to claim 1, characterized in that: The method comprises the following steps: (1) preparing component A; and (2) preparing component B.